2006
DOI: 10.2466/pms.102.1.231-238
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Target Location on Coincident Timing Performance

Abstract: This study examined the influence of two stimulus-presentation methods on coincident timing performance. 50 participants performed a button press and striking task in coincidence with a target stimulus. Participants were randomly divided into either the Terminating Group, whose target light was the last in the series, or the Apparent Motion Group, whose target was not the final light in the series and allowed the apparent motion of the stimulus to continue. 20 trials at each of three velocities, 4, 8, and 12 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 19 publications
(30 reference statements)
1
9
0
3
Order By: Relevance
“…Apresenta-se seguidamente na figura 1 a primeira parte da codificação, a árvore estrutural da categoria "Áreas Estratégicas Municipais" composta pelas subcategorias: gestão financeira e equipamentos desportivos. Contudo, deve-se esclarecer que é reservada aos municípios autonomia administrativa e financeira através do princípio de organização estatal, artigo 263º, n.º 3, da Constituição da República de Moçambique (3) , significando isto, que são responsáveis pela distribuição eficiente dos seus recursos financeiros para os diferentes setores. Não deveria, pois, ao nível municipal deixar de se atribuir ao desporto um orçamento específico.…”
Section: Resultsunclassified
“…Apresenta-se seguidamente na figura 1 a primeira parte da codificação, a árvore estrutural da categoria "Áreas Estratégicas Municipais" composta pelas subcategorias: gestão financeira e equipamentos desportivos. Contudo, deve-se esclarecer que é reservada aos municípios autonomia administrativa e financeira através do princípio de organização estatal, artigo 263º, n.º 3, da Constituição da República de Moçambique (3) , significando isto, que são responsáveis pela distribuição eficiente dos seus recursos financeiros para os diferentes setores. Não deveria, pois, ao nível municipal deixar de se atribuir ao desporto um orçamento específico.…”
Section: Resultsunclassified
“…A duração temporal do estímulo é, assim, um aspecto que deve ser considerado. Meeuwsen, Goode e Goggin (11) , assim como Coker (3) , afirmaram que quando se aumenta a velocidade do estímulo os erros aumentam, ou seja, a diminuição do tempo de visualização do estímulo quando a velocidade é incrementada, conduz a piores desempenhos. Meeuwsen, Goode e Goggin (11)…”
Section: Instrumentosunclassified
“…A terceira explicação relaciona-se com a capacidade de coordenar e modificar as respostas tendo por base o feedback tanto dos processos receptores como dos efectores. A partir dos 15 anos de idade, o adolescente adquire condições de executar uma tarefa de AC de forma equivalente aos adultos (3) . A maior precisão parece situar-se entre os 15 e os 30 anos de idade (1,7,21) .…”
Section: Introductionunclassified
“…Contradictory results for temporal accuracy have been reported. As target speed increased, experiments have found that timing accuracy decreased ( Peters, 1997 ;Abernethy & Neal, 1999 ;Coker, 2006 ), increased ( Peterken, Brown, & Bowman, 1991 ;Long & Vogel, 1998 ;Tresilian & Plooy, 2006 ), or remained unchanged ( Fleury & Bard, 1985 ) with increased target speed. Three interrelated factors may be important for these disparate fi ndings.…”
mentioning
confidence: 99%
“…Three interrelated factors may be important for these disparate fi ndings. Observations that timing errors increase with increased target speed are typically associated with relatively high target speeds, short viewing times, and large biases or constant errors due to late responding at the fastest speeds (e.g., Peters, 1997 ;Coker, 2006 ). In contrast, studies using relatively low target speeds and longer viewing times typically have lower constant errors, and timing errors decrease with increased target speed (e.g., Tresilian & Plooy, 2006 ).…”
mentioning
confidence: 99%